Factors influence dividend policy of public listed companies in Malaysia / Nurr Amiera Nasuha - Nasuha, Nurr Amiera (Faculty of Business Management, 2017)
This study aims to investigate thedeterminants of the dividend policy of public listed companies in Malaysia. The factor examinedin this study includes Earning per share, Cash Flowper share, net profit margin and current ratio. Data were obtained from the relevant databases and annual Data were obtained from the relevant databases and annual reports of the sampled companies. The study examines a total of 25 listed companies during year 2006 until 2015. The results revealed the four factors that is only cash flowper sharehave a significant influenceon dividend policy and earning per share, net profit margin and current ratiohas negative significant effect on dividend policy. The findings from this study are useful to the board of directors and management team of companies in deciding an appropriate dividend policy for the company. The results are also useful to shareholders in making investment decisions.